Representasi Inai pada Tangan Calon Mempelai Wanita dalam Pernikahan Adat - Devy Putri Kussanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Nowadays more and more inserted in the marriage culture is the presence of hand decoration using henna. Although the use of henna is not stated in certain religious or cultural laws, there is a reason used by prospective brides to use henna as decorative accessories on the back of the hand when performing traditional marriages. The difference in meaning in denotation and connotation is the basic basis for the use of henna in traditional wedding processions, this is also seen in the Sumbawa cultural custom processions. This study uses an ethnographic point of view with qualitative descriptive research methods, sources of information obtained from secondary interviews and literature reviews in the form of books and scientific journals that are in accordance with the research. So that an explanation is obtained based on Roland Barhtes' symbol chart regarding the use of henna on the back of the hand of the prospective bride.